Pastoral counseling in Christian schools: A hidden force in shaping professional teachers’ roles beyond the classroom - Da Costa, Augusto; Ximenes, Mateus dos Santos; Rostiawan, Fitra Fajar (Universitas Ahmad Dahlan, 2025)
Spiritual well-being and mental health have become increasingly important issues in modern life, which is often marked by stress and uncertainty. Pastoral counseling emerges as an integrative approach that combines Christian spiritual values, psychological principles, and counseling techniques to holistically support individuals. This article aims to map the development and global trends in pastoral counseling research through a bibliometric analysis of 1,848 Scopus-indexed publications from 1970 to 2025. The study adopts the PRISMA approach for data screening and uses the VOSViewer application to visualise the results. Findings reveal a significant increase in the number of publications, with major contributions from the United States, the United Kingdom, and South Africa, as well as leading authors such as Seward Hiltner and Lindsay B. Carey. Institutions like the University of Pretoria were also noted as active contributors in this field. Collaboration and keyword network analysis show that key emerging themes include spirituality, empathy, emotional healing, and responses to global crises such as the COVID-19 pandemic. The study affirms that pastoral counseling is a dynamic, multidisciplinary field that adapts to the evolving needs of society and remains relevant in shaping transformative pastoral care practices. This article is expected to serve as both an academic and practical reference for further research and the implementation of pastoral counseling across various socio-religious contexts.